Some Star related I-cordial graphs - Nicholas, T.; Maya, P. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
An I-cordial labeling of a graph G = (V, E) is an injective map f from V to *  +or* ⌊⌋ ⌊⌋+ as p is even or odd, respectively be an injective mapping such that f(u) + f(v) ≠ 0and induces an edge labeling f*: E → {0, 1} where, f*(uv) = 1 if f(u) + f(v) > 0 and f*(uv) = 0otherwise, such that the number of edges labeled with1and the number of edges labeled with 0differ at most by 1. If a graph has I-cordial labeling, then it is called I-cordial graph.In thispaper, we prove that Bm,n, S'(Bn,n), D2(Bm,n) are I-cordial; Kn,n is I-cordial only if n is even ; Km,nis I-cordial only if m or n is even and Bn,n2is not I-cordial.